The mediating role of jubilation and academic motivation in the relationship between learning self-direction and social acceptance in female elementary school students in Tonekabon - samira pali; leyla ezani (مدیریت و چشم انداز آموزش, 2020)
The aim of this study was to determine the mediating role of jubilation and academic motivation in the relationship between learning self-direction and social acceptance in female elementary school students in Tonekabon. The research method was descriptive-correlation. The population of this study was female students of the second grade of elementary school in Tonekabon. 204 students were selected by means of cluster random sampling method. Data collection tools were Walland et al.'s Academic Motivation Questionnaire(1992), Crown and Marlowe Social Acceptance Questionnaire(1960), Fisher et al.'s  Learning Self-Guidance Questionnaire(2001), and Oxford Jubilation Questionnaire. Data analysis using structural equation modeling showed that in the research model, the direct effect of the predictor and criterion variables was 0.38, the indirect effect was 0.600 provided that there is a jubilation mediating variable, and the indirect effect was 0.510 provided that there is an academic motivation mediating variable. Thus, due to the lower effect of direct path compared with indirect paths, the existence of mediating variables of jubilation and academic motivation increases the effect, and the mediating role in the research hypothesis was confirmed.